Handbook of Environmental Engineering - Surampalli, Rao; Zhang, Tian C.; Brar, Satinder Kaur; Hegde, Krishnamoorthy; Pulicharla, Rama; Verma, Mausam (McGraw-Hill Education, 2018)
A complete guide to environmental regulations and remediation. This practical resource offers thorough coverage of current environmental issues and policies along with step-by-step remediation procedures. With contributions from dozens of industry-recognized experts, Handbook of Environmental Engineering features information on all segments of the market?including water and air quality and hazardous waste?and enables you to ensure compliance with all applicable regulations. You will get details about sensors, monitoring, and toxicity treatment and controls as well as waste management and safe disposal. Real-world examples demonstrate how to apply techniques and achieve compliance, while environmental impact assessments and measurement data enhance the book's utility.